The lion inside - Bright, Rachel; Field, Jim (London orchard books, 2017)
Board book edition of this bestselling story about confidence, self-esteem, and a shy little mouse who sets out on a journey to find his roar
English stories
Keywords: Lion Juvenile fiction; English stories